Severe Conjunctivitis Due to Multidrug‐Resistant Neisseria gonorrhoeae and Adenovirus 53 Coinfection in a Traveler Returning From Thailand. Issue 6 (10th October 2013) - Tappe, Dennis; Mueller, Andreas; Weißbrich, Benedikt; Schubert, Jörg; Schargus, Marc; Stich, August
Abstract : A male traveler returning from Thailand with severe bilateral conjunctivitis was tested for causative pathogens by culture and polymerase chain reaction in late 2010. The culturally grown Neisseria gonorrhoeae strain was resistant against penicillin, ciprofloxacin, and tetracycline. The patient was also found to have an eye infection with the unusual and likely recombinant adenovirus type 53. Besides multidrug‐resistant gonococcal strains the unusual adenovirus strain is found circulating in Asia and both pathogens may be a risk for travelers.